2008
DOI: 10.1091/mbc.e08-05-0513
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Mammalian P Body Transport, Assembly, and Disassembly In Vivo

Abstract: Exported mRNAs are targeted for translation or can undergo degradation by several decay mechanisms. The 533 degradation machinery localizes to cytoplasmic P bodies (PBs). We followed the dynamic properties of PBs in vivo and investigated the mechanism by which PBs scan the cytoplasm. Using proteins of the decapping machinery, we asked whether PBs actively scan the cytoplasm or whether a diffusion-based mechanism is sufficient. Live-cell imaging showed that PBs were anchored mainly to microtubules. Quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

31
218
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 217 publications
(257 citation statements)
references
References 56 publications
31
218
3
1
Order By: Relevance
“…Interestingly, in about 50% of the cases PBs were found adjacent to mRNPs as if the two entities were docked to each other. In this study 29 and in our study, 18 PBs were not found associated with other organelles such as mitochondria, endoplasmatic reticulum and peroxisomes, but did associate with stress granules that are also RNA-containing structures. Chemical synaptic stimulation of neurons led to a substantial decrease in dendritic PBs, which returned to normal levels after a 30 minute period.…”
supporting
confidence: 49%
See 2 more Smart Citations
“…Interestingly, in about 50% of the cases PBs were found adjacent to mRNPs as if the two entities were docked to each other. In this study 29 and in our study, 18 PBs were not found associated with other organelles such as mitochondria, endoplasmatic reticulum and peroxisomes, but did associate with stress granules that are also RNA-containing structures. Chemical synaptic stimulation of neurons led to a substantial decrease in dendritic PBs, which returned to normal levels after a 30 minute period.…”
supporting
confidence: 49%
“…Fluorescence recovery after photobleaching (FRAP) has shown that most PB components are constantly exchanging between PBs and the cytoplasm, 16,17,35 except for the decapping enzyme Dcp2 that did not exchange. 18 This suggests that Dcp2 is a core component of PBs. However, when there is no microtubule network, this control is overrun and most of the Dcp proteins can now assemble into large PBs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…29,30,[32][33][34][35] PBs are extremely dynamic, changing in size and number in response to cell cycle stage, nutrient availability, and stresses such as ultraviolet light (UV), osmotic shock and other inhibitors of global translation. 27,33,35,36 PBs can also transiently associate and exchange cargo with stress granules (SGs), cytoplasmic foci that triage stalled translationally-competent mRNPs. 34 PB assembly and disassembly is influenced by changes in the degradative capacity of the cell; for example, when 5 0 -3 0 exonucleolytic decay is prevented, the resulting accumulation of cytoplasmic mRNA awaiting destruction causes PB size and number to increase, whereas inhibiting de novo transcription or halting translation by trapping mRNA in polysomes has the opposite effect.…”
Section: Processing Bodies Control Inflammatory Mediator Release By Ecsmentioning
confidence: 99%
“…37,38 PBs also maintain a dynamic relationship with the cytoskeleton; stationary PBs associate with actin bundles whereas mobile PBs connect to the microtubule network. 36,39,40 Though PB formation was recently shown to be modified by the cytoskeletal regulator RhoA, 22,27,28 the precise mechanism of action remains to be elucidated.…”
Section: Processing Bodies Control Inflammatory Mediator Release By Ecsmentioning
confidence: 99%